Rai rai rai. 1 - Yoshiaki (Shōnen Sandē komikkusu., 2025)
"Humanity might've triumphed over the aliens, but that didn't stop struggling space exterminator Sumire Ichigaya from getting abducted by a UFO! After being implanted with a foul-mouthed extraterrestrial entity, she's got a lot more to worry about that just paying her bills. Sumire Ichigaya's got it tough. She's drowning in debt, surrounded by noisy neighbors, fighting for discount supermarket meals, and working a dead-end job exterminating space vermin left over from a failed alien invasion. It seems like things just can't get any worse--until she's abducted by aliens and wakes up with a monstrous new arm and a voice in her head urging her to kill all of humanity!"--page [4] of cover.